Epidemiological analyses of tuberculosis in Archangelsk, Russia and implementation of a rapid assay for detection of resistance in this high burden setting - Eliseev, Platon I; Maryandyshev, Andrey O; Nikishova, Elena I; Tarasova, Irina V; Gorina, Galina P; Chryssanthou, Erja; Ridell, Malin; Larsson, Lars-Olof (International journal of mycobacteriology, 2013)
Abstract Background Tuberculosis (TB) is a major problem in Russia, particularly regarding multidrug-resistant tuberculosis (MDR-TB). Rapid drug susceptibility testing methods are therefore needed. Objectives To perform epidemiological analyses of TB in the Archangelsk region and to evaluate the molecular method GenoType®MTBDR plus in this type of setting. Materials and methods Clinical and microbiological data of all TB patients in Archangelsk were collected in 2010. Smear-positive sputa were analysed by MTBDR plus and Bactec MGIT 960. Results The number of TB cases was 812 (incidence 65/105) and among these patients, 151 cases were registered in the penitentiary system (incidence 1162/105). Most patients were men, 94% had pulmonary TB and 22% were relapses. Out of all cases, 341 (42%) were smear positive and thus contagious and 176 (22%) had MDR-TB, among which one had extensively drug resistant tuberculosis (XDR-TB). Furthermore, two TB patients had strains being resistant to rifampicin, but susceptible to isoniazid. The number of cases being both contagious and MDR-TB was 128 representing 15.8% of all TB cases (incidence 10.2/105). Among these 128 TB patients 37 were relapses representing 25.7% of all the relapse cases. The results of MTBDR plus and Bactec MGIT analyses corresponded in 98.8%. Conclusions In Archangelsk many TB patients had contagious MDR-TB thus being hazardous in society and relapsing pulmonary TB was common. The TB situation in the prisons was particularly severe. The analyses showed furthermore that MTBDR plus is of major value in this setting.